Políticas regulatorias aplicadas a sectores de infraestructura en Argentina - Gustavo Ferro; Andrea Castellano; Celeste Chaz Sardi (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2020)
– We study the recent evolution of the utilities services and regulation in Argentina. We focus, after a global approach to the issue in four domiciliary services: electricity, natural gas by piped network, telecommunications and water and sanitation. We show the changing policy approach and the failure to successive contradictory policies. We highlight the connection between these failures in having self-financing, efficient and affordable services, and macroeconomic problems, particularly, the use of tariff control as an anti-inflationary tool.
Keywords: 330; Regulation; Utilities; Infrastructure; Argentina